2022
DOI: 10.1213/ane.0000000000006149
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Strategies for Hemostatic Blood Products in Critically Ill Children: A Narrative Review and Update on Expert Consensus Guidelines

Abstract: Critically ill children commonly receive coagulant products (plasma and/or platelet transfusions) to prevent or treat hemorrhage or correct coagulopathy. Unique aspects of pediatric developmental physiology, and the complex pathophysiology of critical illness must be considered and balanced against known transfusion risks. Transfusion practices vary greatly within and across institutions, and high-quality evidence is needed to support transfusion decision-making. We present recent recommendations and expert co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 131 publications
0
17
0
Order By: Relevance
“…Emerging evidence has shown that some transfusion practices are harmful for certain NICU patients, such as platelet transfusions in preterm infants 5,6 . More broadly, transfusion reactions can occur with virtually all blood products 7 and these reactions are likely under-diagnosed, underestimated, and under-reported in pediatric patients 3 . Our intention was to establish optimal transfusion guidelines for our division and neonatal network, including 19 hospitals, based on a review of currently available literature.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has shown that some transfusion practices are harmful for certain NICU patients, such as platelet transfusions in preterm infants 5,6 . More broadly, transfusion reactions can occur with virtually all blood products 7 and these reactions are likely under-diagnosed, underestimated, and under-reported in pediatric patients 3 . Our intention was to establish optimal transfusion guidelines for our division and neonatal network, including 19 hospitals, based on a review of currently available literature.…”
Section: Introductionmentioning
confidence: 99%
“…It largely justifies the threshold for more invasive intervention after a resuscitative threshold is met in injured children (over 40 mL/kg within the first 24 hours was associated with excess in-hospital mortality). It has been referenced by the ATOMAC (Arizona, Texas, Oklahoma, Memphis, Arkansas Consortium) trauma consortium,8 and other consensus guidelines 9. In total, it has been cited 149 times to date.…”
mentioning
confidence: 99%
“…Given that plasma and/or platelet transfusions are associated with adverse reactions (ie, febrile, hypotensive, allergic and anaphylactic reactions [FAHR], transfusion-related acute lung injury [TRALI], transfusion-associated circulatory overload [TACO], and transfusion-related immunomodulation [TRIM]), following these strategies should positively impact pediatric patient outcomes. 15…”
mentioning
confidence: 99%
“…14 Expert consensus was lacking until recently when considering the management of hemostatic blood components. Management guidelines for transfusion of hemostatic blood components, such as plasma, platelets, cryoprecipitate, and recombinant products in pediatrics, are summarized by Valentine et al 15 This review provides recommendations to direct clinicians in the decision to transfuse or not to transfuse hemostatic blood components to critically ill children. Given that plasma and/or platelet transfusions are associated with adverse reactions (ie, febrile, hypotensive, allergic and anaphylactic reactions [FAHR], transfusion-related acute lung injury [TRALI], transfusion-associated circulatory overload [TACO], and transfusion-related immunomodulation [TRIM]), following these strategies should positively impact pediatric patient outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation